Gaining access through a calcified pulp chamber: a clinical challenge - Ngeow, Wei Cheong; Thong, Y.L. (Wiley, 1998)
Dental pulp is prone to dystrophic mineralization; this mineralization can be so extensive that the entire root canal system is obliterated, As a result, root canal treatment can become a difficult if not impossible task, This article presents the endodontic management of a tooth with an obliterated pulp chamber and associated with a discharging sinus in a teenage patient, The role of a calcium hydroxide lining to induce mineralization and cause the obliteration of the pulpal space is also discussed.